Carbon–Silica Composites to Produce Highly Robust Thin‐Film Electrochemical Microdevices. Issue 12 (20th October 2017) - Niu, Pengfei; Asturias‐Arribas, Laura; Jordà, Xavier; Goñi, Alejandro R.; Roig, Anna; Gich, Martí; Fernández‐Sánchez, César
Abstract: Carbonaceous materials are extensively applied to the development of electrochemical devices for electroanalysis, energy conversion, and storage or electrocatalysis because of their rather unique features that include high chemical stability, low cost, and wide potential window. Furthermore, they are processed into thick or thin‐film structures onto different substrates for producing electrode devices whose widespread use, however, is hampered by the film composition and the poor mechanical stability. Here the application of carbon/silica composites is shown to produce miniaturized thin‐film electrodes, which stand out for their robustness and can thus be used repeatedly for electrochemical analysis. Resorcinol‐formaldehyde/(3‐aminopropyl)triethoxysilane sol–gel films on silicon substrates are subjected to several processes that combine lithography, etching, and pyrolysis steps to yield carbon/silica thin‐film electrodes, at wafer scale. The presence of silica in the electrode material promotes strong interfacial adhesion to the substrate, dramatically increasing the number of measurements a single electrode can withstand without loss of performance. The thorough electroanalytical characterization by cyclic voltammetry in solutions containing representative redox species reveals an electrode performance comparable to that of glassy carbon for outer‐sphere redox processes. In addition, the modification of the electrode surface with metal nanoparticles allows for the sensitive detection of heavy metal ion pollutants. Abstract : Carbon–silica composite thin‐films to produce electrode devices that withstand more than a hundred electrochemical measurements in liquid solutions without loss of performance thanks to the strong adhesion of the silica component to the substrate. These devices are applied in electrochemical sensing but can also find application in energy storage and electrocatalysis.